Effect of guanidine acetic acid on meat quality, muscle amino acids, and fatty acids in Tibetan pigs - Cui, Yiyan; Tian, Zhimei; Yu, Miao; Liu, Zhichang; Rong, Ting; Ma, Xianyong (Frontiers in Veterinary Science, 2022)
This study investigated the effects of guanidine acetic acid (GAA) supplementation on growth performance, carcass traits, and meat quality in Tibetan pigs. A total of 18 male Tibetan pigs (21.35±0.99 kg) were randomly assigned to the control (basal diet) and GAA (basal diet + 800 mg/kg GAA) groups for 125 days. Growth performance, carcass traits, and meat quality in pigs, and the chemical composition of longissimus thoracis (LT) were not altered by GAA. In LT, compared to the control group, dietary GAA increased the superoxide dismutase activity, transcripts of stearoyl CoA desaturase (SCD) and fatty acid synthase (FAS), and contents of glutamate, glutamine, C24:0, C20:3n-6, C20:4n-6, and polyunsaturated fatty acids (P < 0.05), but it decreased the malondialdehyde content (P < 0.001). In back fat, dietary GAA reduced the transcript of peroxisome proliferator-activated receptor γ (PPARγ) and the contents of C10:0, C12:0, C14:0, and C16:0 (P< 0.05), whereas it increased the contents of C22:0, C20:1, C22:1, C24:1, C20:2, C20:3n-3, and C22:2 (P < 0.05). These findings will provide a basis for high-quality Tibetan pork production.